Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
mình ko ấn dấu lim, bn tự biết thêm vào nhé:
\(\frac{x^2-4x+3}{\sqrt{4x+5}-3}=\frac{\left(x-3\right)\left(x-1\right)\left(\sqrt{4x+5}+3\right)}{4x-4}=\frac{\left(x-3\right)\left(\sqrt{4x+5}+3\right)}{4}=-3\)
Giải:
Ta có: \(\frac{x-2}{5}=\frac{2x-3}{4}\)
\(\Rightarrow\left(x-2\right).4=5.\left(2x-3\right)\)
\(\Rightarrow4x-8=10x-15\)
\(\Rightarrow4x-10x=8-15\)
\(\Rightarrow-6x=-7\)
\(\Rightarrow x=\frac{7}{6}\)
Vậy \(x=\frac{7}{6}\)
Giải :
Ta có : \(\frac{x-2}{5}=\frac{2x-3}{4}\)
\(\Rightarrow\left(x-2\right),4=5,\left(2x-3\right)\)
\(\Rightarrow4x-8=10x-15\)
\(\Rightarrow4x-10x=8-15\)
\(\Rightarrow-6x=-7\)
\(\Rightarrow x=\frac{7}{6}\)
Vậy \(x\) là \(\frac{7}{6}\)
\(I_1=\int cos\left(\frac{\pi x}{2}\right)dx-\int\frac{2}{6x+5}dx=\frac{2}{\pi}\int cos\left(\frac{\pi x}{2}\right)d\left(\frac{\pi x}{2}\right)-\frac{1}{3}\int\frac{d\left(6x+5\right)}{6x+5}\)
\(=\frac{2}{\pi}sin\left(\frac{\pi x}{2}\right)-\frac{1}{3}ln\left|6x+5\right|+C\)
\(I_2=-\frac{1}{2}\int\left(4-x^4\right)^{\frac{1}{2}}d\left(4-x^4\right)=-\frac{1}{2}.\frac{\left(4-x^4\right)^{\frac{3}{2}}}{\frac{3}{2}}+C=\frac{-\sqrt{\left(4-x^4\right)^3}}{3}+C\)
\(I_3=2\int e^{\frac{1}{2}\left(4+x^2\right)}d\left(\frac{1}{2}\left(4+x^2\right)\right)=2e^{\frac{1}{2}\left(4+x^2\right)}+C=2\sqrt{e^{4+x^2}}+C\)
\(I_4=-\frac{1}{2}\int\left(1-x^2\right)^{\frac{1}{3}}d\left(1-x^2\right)=-\frac{1}{2}.\frac{\left(1-x^2\right)^{\frac{4}{3}}}{\frac{4}{3}}+C=-\frac{3}{8}\sqrt[3]{\left(1-x^2\right)^4}+C\)
\(I_5=\int e^{sinx}d\left(sinx\right)=e^{sinx}+C\)
\(I_6=\int\frac{d\left(1+sinx\right)}{1+sinx}=ln\left(1+sinx\right)+C\)
\(I_7=\int\left(x+1\right)\sqrt{x-1}dx\)
Đặt \(\sqrt{x-1}=t\Rightarrow x=t^2+1\Rightarrow dx=2tdt\)
\(\Rightarrow I_7=\int\left(t^2+2\right).t.2t.dt=\int\left(2t^4+4t^2\right)dt=\frac{2}{5}t^5+\frac{4}{3}t^3+C\)
\(=\frac{2}{5}\sqrt{\left(1-x\right)^5}+\frac{4}{3}\sqrt{\left(1-x\right)^3}+C\)
\(I_8=\int\left(2x+1\right)^{20}dx\)
Đặt \(2x+1=t\Rightarrow2dx=dt\Rightarrow dx=\frac{1}{2}dt\)
\(\Rightarrow I_8=\frac{1}{2}\int t^{20}dt=\frac{1}{42}t^{21}+C=\frac{1}{42}\left(2x+1\right)^{21}+C\)
\(I_9=-3\int\left(1-x^3\right)^{-\frac{1}{2}}d\left(1-x^3\right)=-3.\frac{\left(1-x^3\right)^{\frac{1}{2}}}{\frac{1}{2}}+C=-6\sqrt{1-x^3}+C\)
\(I_{10}=\int\frac{x}{\sqrt{2x+3}}dx\)
Đặt \(\sqrt{2x+3}=t\Rightarrow x=\frac{1}{2}t^2-\frac{3}{2}\Rightarrow dx=t.dt\)
\(\Rightarrow I_{10}=\int\frac{\frac{1}{2}t^2-\frac{3}{2}}{t}.t.dt=\frac{1}{2}\int\left(t^2-3\right)dt=\frac{2}{3}t^3-\frac{3}{2}t+C\)
\(=\frac{2}{3}\sqrt{\left(2x+3\right)^3}-\frac{3}{2}\sqrt{2x+3}+C\)
\(I=\int\limits^0_{\frac{-1}{2}}\frac{dx}{\left(x+1\right)\sqrt{3+2x-x^2}}=\int\limits^0_{\frac{-1}{2}}\frac{dx}{\left(x+1\right)\left(\sqrt{\left(x+1\right)\left(3-x\right)}\right)}\)
\(=\int\limits^0_{\frac{-1}{2}}\frac{dx}{\left(x+1\right)^2\sqrt{\frac{3-x}{x+1}}}\)
Đặt \(t=\sqrt{\frac{3-x}{x+1}}\Rightarrow\frac{dx}{\left(x+1\right)^2}=-\frac{1}{2}\)
Đổi cận : \(x=-\frac{1}{2}\Rightarrow t=\sqrt{7};x=0\Rightarrow t=\sqrt{3}\)
\(I=-\frac{1}{2}\int\limits^{\sqrt{3}}_{\sqrt{7}}dt=\frac{1}{2}\left(\sqrt{7}-\sqrt{3}\right)\)